The THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND WORK STRESS AND EMPLOYEE PERFORMANCE - Sinlae, Edwin Reinhard; Lerik, Mariana Dinah Ch.; Damayanti, Yeni (Journal of Health and Behavioral Science, 2024)
In the age of globalization as it is today, companies are challenged to compete effectively and efficiently in an ever-tightening market. This leads to increased pressure on the employees who work in the company. The process of achieving high employee performance requires the support of high emotional intelligence of employees to perform tasks well and be accountable for them. Emotional intelligence and work stress are related, because when employees feel stressed due to the existing workload, they need to be able to keep their emotions positive and use their emotions as their own motivation to perform their tasks well. In this study, quantitative research methods were used with a correlational research approach. A questionnaire with performance scales, emotional intelligence and work stress scales with a total of 49 questions was used for data collection. Dedicated grab samples were collected in this study and 81 samples were collected. Data analysis techniques that use assumption tests (normality tests, multicollinearity tests, and heteroscadastic tests) and hypothesis tests (partial tests, simultaneous tests, and determination coefficient analysis). The results showed that there was a significant association between the emotional intelligence variables and the performance variables of the employees, resulting from the results of the t-count (8,936) > t-table 1,990 with sig values. 0.000< 0.05 and there is no significant correlation between the variables for work stress and the performance variables of employees resulting from the results of the t-number (0.457) < t-table 1.990.